The Introduction of the Euro and Inflation Cross-country Differences in Perceived Inflation - Svobodová, Lucie (2012)
This dissertation thesis examines the divergence of perceived inflation, measured by the EU Consumer Surveys, and officially measured inflation after the introduction of cash euro in several eurozone countries. Two groups of countries are tested in the thesis -- countries accepting the euro in 2002 and countries providing the changeover in later years. The main goal of the thesis is to test cross-country differences between officially measured and perceived inflation with respect to economic, social and cultural specifics of the countries in the eurozone, while main focus is given to examining the differences between the above-mentioned two groups of countries. The results obtained could help to derive policy conclusions for the other EU countries which have not yet accepted the common currency.